Cavity 3D modeling and correlative techniques based on cavity monitoring - Luo, Zhou-quan; Liu, Xiao-ming; Zhang, Bao; Lu, Hao; Li, Chang (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2008)
According to the mining method for Dongguashan Copper Mine and Tongkeng Mine in China, and with the help of the cavity monitoring system(CMS) and mining software Surpac, the 3D cavity models were established exactly. A series of correlative techniques for calculating stope over-excavation and under-excavation, stope dilution and ore loss rates, and the blasting design of the pillar with complicated irregular boundaries were developed. These techniques were applied in Dongguashan Copper Mine and Tongkeng Mine successfully. Using these techniques, the dilution rates of stopes 52-2 # , 52-6 # , 52-8 # and 52-10 # of Dongguashan Copper Mine are calculated to be 2.12%, 8.46%, 12.67% and 10.68%, respectively, and the ore loss rates of stopes 52-6 # and 52-8 # are 4.41% and 3.70%, severally. Furthermore, according to the design accomplished by the technique for a pillar of Tongkeng Mine with irregular boundary, the volume, total length of boreholes and the dynamite quantity of the pillar are computed to be 1.2 × 10 4 m 3 , 2.98 km and 10.97 t, correspondingly.